Criticizing global governance - Lederer, Markus, 1972-; Müller, Philipp S. (Palgrave Macmillan, 2005)
This collection reflects on global governance and provides a better critical understanding of the various practices that fall under its rubric. The first part challenges the concept of global governance, the next focuses on organizational and institutional aspects, and finally the rule systems implemented by global governance practices is examined.